Educational transformation : is it a myth? - Mohd. Nasir, Nora (IATED, 2012)
Many university students upon or after graduation find themselves asking the question, “What did we learn while we were studying at the university?” and most of the time they are unable to give a clear and definite answer to that question. The purpose of the study was to gain insights into the undergraduate experience of five students in their final year at the International Islamic University in Malaysia. Through the use of a qualitative phenomenological study, these five students were interviewed one-on-one and were also asked to write down some of their thoughts about their experiences via email. A short questionnaire was emailed to each of them four months after they graduated to see whether there were any developments in the way they perceived and defined their undergraduate experience. Results of the interviews provided essential descriptions of the participants’ experience which were found to be also consistent with student development theories. All five students acknowledged the fact that the class lessons were interesting and enjoyable, but were frustrated because they were not encouraged to speak up, let alone voice their opinions. Through developing a deeper understanding of what these students were trying to say, the study has implications for university lecturers and administrators interested in improving the quality of the undergraduate experience.